2018
DOI: 10.1007/s10995-018-2558-2
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Postpartum Contraception Counseling at the Well Baby Visit

Abstract: Objectives The postpartum period is a high-risk time for unintended pregnancy, and additional opportunities to provide contraception are needed. Our objective was to evaluate the acceptability of providing postpartum contraceptive counseling at a pediatric well baby visit, and compare it to counseling at the routine postpartum visit. Methods Postpartum women (100 per group) were recruited for this cohort study at pediatric well baby visits and obstetric postpartum visits at an academic medical center. Well bab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Maternal depression screening at the WBV is already a reimbursable service through the child's Medicaid 20 . In addition to depression screening at the WBV, family practice practitioners 21 and other practitioners 3 have begun to introduce additional screening tools at the WBV to address women's health needs including smoking cessation, folic acid supplementation, and contraception 21‐24 . Research has already demonstrated that women and physicians are receptive to colocating maternal contraception services with pediatric care 3,11,23,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal depression screening at the WBV is already a reimbursable service through the child's Medicaid 20 . In addition to depression screening at the WBV, family practice practitioners 21 and other practitioners 3 have begun to introduce additional screening tools at the WBV to address women's health needs including smoking cessation, folic acid supplementation, and contraception 21‐24 . Research has already demonstrated that women and physicians are receptive to colocating maternal contraception services with pediatric care 3,11,23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to depression screening at the WBV, family practice practitioners 21 and other practitioners 3 have begun to introduce additional screening tools at the WBV to address women's health needs including smoking cessation, folic acid supplementation, and contraception 21‐24 . Research has already demonstrated that women and physicians are receptive to colocating maternal contraception services with pediatric care 3,11,23,24 . Delivery of some aspects of women's health care in conjunction with the WBV is not meant to supersede the postpartum visit with a woman's prenatal care practitioner; however, for women who are not able to access their own PP care, the WBV practitioner can screen for women's health needs and appropriately refer back to the prenatal care/postpartum practitioner or other practitioners as needed.…”
Section: Discussionmentioning
confidence: 99%
“…Linking contraceptive services with infant care in primary care is another strategy explored internationally to optimise the provision of postpartum contraception (Caskey et al 2016;Kumaraswami et al 2018;Haider et al 2020), which could be implemented in Australia. In Australia, each state/ territory has its own maternal and child health (MCH) service where community nurses provide care during a child's development from 0 to 5 years (Raising Children 2022).…”
Section: Co-location Of Services Postnatallymentioning
confidence: 99%
“…Contraception counselling in conjunction with infant care is generally acceptable to postpartum women (Fagan et al 2009;Caskey et al 2016;Kumaraswami et al 2018). Although this strategy does have limitations, including the often limited time available during well-baby visits (Caskey et al 2016) and the brief shift in focus away from the infant (Henderson et al 2016), co-locating contraceptive care with infant care may be acceptable to many women and improve accessibility to postpartum contraception (Kumaraswami et al 2018). In one American study, 95% of mothers felt comfortable discussing contraception with their infants' providers, and 79% reported being very likely to use a contraception prescription obtained at the well-baby visit (Kumaraswami et al 2018).…”
Section: Co-location Of Services Postnatallymentioning
confidence: 99%
See 1 more Smart Citation